Data-Driven Finance in Multinational Corporations : Prague in Focus - Suresh, Vipassana; Kučera, Jan; Potančok, Martin; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2025)
This thesis focuses on the status of data analytics adoption in the finance departments of multinational corporations located in Prague and its impact on management reporting processes. In this regard, the thesis aims to provide insights into these research questions: an analysis of the maturity of data analytics, management reporting effectiveness, and data visualization's role. Hence, this research will also explain how data analytics can be optimized to realize better financial decision-making. It will analyze the challenges and opportunities of using data analytics in finance for decision-making. The research shall identify best practices, pinpoint several needs of multinational companies, and provide actionable recommendations on improving financial performance using data-driven insights. Through qualitative and quantitative research methods, this paper displays valuable insights into the current state of data analytics usage within finance departments, the influence of data analytics on management reporting processes, and the role of data visualization in supporting financial decisions. Findings from this research will contribute to the knowledge base in data analytics and their applications to financial management.
Vedoucí práce: Jan Kučera
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: management of business informatics [obor dipl. práce]; diplomové práce; master's theses